COMMUNITY SERVICE THROUGH THE LITERACY VILLAGE MODEL READING GARDEN IN DESA SUKAMULYA - Tasya Amelia; Riska Novita Sari; Susi Fitri Alawiah; Titin Surnayati (JOURNAL INCLUSIVE SOCIETY COMMUNITY SERVIES, 2024)
The reading, numeracy and science knowledge of Indonesian children is below that of Singapore, Vietnam, Malaysia and Thailand based on the results of the PISA (The Program for International Student Assessment) test released by the Organization for Economic Co-operation and Development (OECD) in 2016. Meanwhile 70% of adults in Jakarta only have the ability to understand information from short writing, but have difficulty understanding information from longer and more complex writing. And 86% of adults in Jakarta can only solve arithmetic problems that require one step, but have difficulty completing calculations that require several steps. This data was concluded from the results of the PIAAC (The Program for the International Assessment of Adult Competencies) assessment, a voluntary competency test for adults aged 16 years and over